2009
DOI: 10.1016/j.immuni.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Repressor Bcl-6 Directs T Follicular Helper Cell Lineage Commitment

Abstract: Follicular helper T (Tfh) cells provide selection signals to germinal center B cells, which is essential for long-lived antibody responses. High CXCR5 and low CCR7 expression facilitates their homing to B cell follicles and distinguishes them from T helper 1 (Th1), Th2, and Th17 cells. Here, we showed that Bcl-6 directs Tfh cell differentiation: Bcl-6-deficient T cells failed to develop into Tfh cells and could not sustain germinal center responses, whereas forced expression of Bcl-6 in CD4(+) T cells promoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
1,155
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,058 publications
(1,215 citation statements)
references
References 56 publications
42
1,155
2
Order By: Relevance
“…Interestingly, Tfh cell differentiation relies on a set of transcription factors including Bcl6, BLIMP1, and IRF4 that also control late stages of B‐cell development. Bcl6 is essential for the induction of Tfh cell differentiation as the reciprocal repression of Bcl6 and BLIMP1 controls the development of Tfh vs. non‐Tfh CD4 + T helper cell populations (Johnston et al , 2009; Nurieva et al , 2009; Yu et al , 2009). At later stages, Bcl6 is required for stable Tfh effector commitment and the maintenance of memory Tfh cells (Liu et al , 2012; Ise et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Tfh cell differentiation relies on a set of transcription factors including Bcl6, BLIMP1, and IRF4 that also control late stages of B‐cell development. Bcl6 is essential for the induction of Tfh cell differentiation as the reciprocal repression of Bcl6 and BLIMP1 controls the development of Tfh vs. non‐Tfh CD4 + T helper cell populations (Johnston et al , 2009; Nurieva et al , 2009; Yu et al , 2009). At later stages, Bcl6 is required for stable Tfh effector commitment and the maintenance of memory Tfh cells (Liu et al , 2012; Ise et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…SAP expression is essential for GC formation,135 preventing inhibitory signaling through SLAM family member 6 (SLAMF6) to enable Tfh‐B cell adhesion,136 which is crucial for Tfh cell retention in GCs and provision of help to B cells. Bcl6 plays a central role in Tfh cell differentiation,115, 137, 138 but other transcription factors that act upstream and downstream of Bcl6 are also required (reviewed in 139). These include lymphoid enhancer‐binding factor 1 (LEF‐1) and T‐cell‐specific transcription factor 1 (TCF‐1), which act upstream of Bcl6 to promote Tfh cell differentiation140, 141, 142; basic leucine zipper transcription factor ATF‐like (Batf), which positively regulates Bcl6 and is important for IL‐4 expression143; interferon regulatory factor 4 (IRF4), which drives differentiation of IL‐12‐stimulated CD4 T cells to Tfh rather than Th1 cells144; achaete‐scute homolog 2 (Ascl2), which induces CXCR5 expression145; c‐Maf, which enhances expression of CXCR5, IL‐21, and IL‐4146; signal transducer and activator of transcription (STAT)s, STAT3 and 4 being particularly important for human Tfh cell differentiation and regulation of IL‐21 expression by human CD4 + T cells121, 147; and forkhead box protein O1 (FOXO1), which can both promote and inhibit Tfh cell differentiation 148.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%
“…Recent work revealed that Bcl6 is also needed for follicular T helper cell development [10][11][12]. Analyses of Bcl6 target genes in B cells indicate that suppression of apoptosis and cell cycle arrest responses occur through p53, p21 and CHEK1 and Bcl6 also regulates DNA damage responses by controlling ATR [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%